2022
DOI: 10.3389/fonc.2022.807102
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Sorafenib Combined With Immunotherapy Following Transarterial Chemoembolization for Advanced Hepatocellular Carcinoma: A Propensity Score Analysis

Abstract: AimThe aim of the study is to compare the efficacy and safety of monotherapy with a sequential immune checkpoint inhibitor (ICI) programmed cell death protein-1 (PD-1) and its combination with multi-target drug sorafenib after transcatheter arterial chemoembolization (TACE) for advanced hepatocellular carcinoma (HCC).MethodsWe conducted a retrospective evaluation of patients with advanced HCC who had received sequential PD-1 sorafenib (duplex group, n = 25) or monotherapy PD-1 alone (PD-1 group, n = 41) after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…TACE only worked on intrahepatic lesions, and had no effect on extrahepatic metastasis; thus, combination with systemic therapy is necessary ( 61 ). In addition, TACE could lead to necrosis of tumor tissue and upregulate the expression of hypoxia-inducible factor 1-α (HIF-1α), vascular endothelial growth factor (VEGF), and fibroblast growth factor (FGF), which could stimulate tumor recurrence or growth ( 2 , 34 , 42 , 61 ). However, lenvatinib administration after TACE could suppress the effects of angiogenic factors ( 2 , 40 ).…”
Section: Why the Combination Therapy Of Lenvatinib Plus Tace With Pd-...mentioning
confidence: 99%
“…TACE only worked on intrahepatic lesions, and had no effect on extrahepatic metastasis; thus, combination with systemic therapy is necessary ( 61 ). In addition, TACE could lead to necrosis of tumor tissue and upregulate the expression of hypoxia-inducible factor 1-α (HIF-1α), vascular endothelial growth factor (VEGF), and fibroblast growth factor (FGF), which could stimulate tumor recurrence or growth ( 2 , 34 , 42 , 61 ). However, lenvatinib administration after TACE could suppress the effects of angiogenic factors ( 2 , 40 ).…”
Section: Why the Combination Therapy Of Lenvatinib Plus Tace With Pd-...mentioning
confidence: 99%
“…[219][220][221] In the clinic, TACE has been combined with immunotherapy to treat HCC, which improved the clinical outcome compared to TACE alone. [222][223][224] However, the systemic administration of immune checkpoint inhibitors (e.g., anti-PD-L1, anti-PD-1) causes substantial systemic adverse effects with compromised therapeutic effects, which undoubtedly limit their wide application in the clinic. [225,226] Hydrogels are favorable to be used as a drug depot to encapsulate immunotherapy drug and facilitate the local immunomodulation of the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies ( 13 , 14 ) have shown that TACE combined with anti-angiogenic therapy and immunotherapy can improve the treatment efficacy of patients with unresectable HCC, with an ORR of approximately 35%–59% and median overall survival (OS) of approximately 13–35 months. Few studies have been conducted using TACE along with apatinib and camrelizumab for patients with unresectable HCC.…”
Section: Introductionmentioning
confidence: 99%